2007
DOI: 10.1124/dmd.107.015909
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Glucuronidation of 5-(4′-Hydroxyphenyl)-5-phenylhydantoin by Human UDP-Glucuronosyltransferase (UGT) 1A1, UGT1A9, and UGT2B15: Effects of UGT-UGT Interactions

Abstract: and UGT1A9. However, the interaction did not alter the stereoselectivity. In conclusion, we found that 4-HPPH O-glucuronide formation in human liver microsomes is catalyzed by UGT1A1, UGT1A9, and UGT2B15 in a stereoselective manner, being modulated by interaction with other UGT1A isoforms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…Thereafter, the formation of various hetero-oligomers was described by means of several techniques. UGT1A1, UGT1A4, UGT1A6, and UGT1A9 have been found to form both homodimers and heterodimers (Fujiwara et al, 2007a,b;Nakajima et al, 2007). UGT1A1 was further demonstrated to interact with all members of the UGT1A family (Operaña and Tukey, 2007) and more recently with its i2 isoform, UGT1A1_i2 .…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, the formation of various hetero-oligomers was described by means of several techniques. UGT1A1, UGT1A4, UGT1A6, and UGT1A9 have been found to form both homodimers and heterodimers (Fujiwara et al, 2007a,b;Nakajima et al, 2007). UGT1A1 was further demonstrated to interact with all members of the UGT1A family (Operaña and Tukey, 2007) and more recently with its i2 isoform, UGT1A1_i2 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the binding affinities of substrates and catalytic efficiency are different between the four isoforms. Furthermore, some substrates are specific for certain UGT1A enzyme as follows: 5-(4Ј-hydroxyphenyl)-5-phenylhydantoin (UGT1A9) (Nakajima et al, 2007), phenylbutazone (UGT1A9) (Nishiyama et al, 2006), and 3-hydroxydesloratadine (UGT1A8) (Ghosal et al, 2004). By a sequence alignment analysis, 14 amino acid residues (Cys3, Arg42, Lys91, Ala92, Tyr106, Gly111, Tyr113, Asp115, Asn152, Leu173, Leu219, His221, Arg222, and Glu241) were found to be specific to UGT1A9 in comparison with UGT1A7, UGT1A8, and UGT1A10 ( Fig.…”
mentioning
confidence: 99%
“…Moreover, it has been reported that protein interaction between UGT and UGT or CYP in microsomes might cause changes in its enzyme activity and stereoselectivity. [21][22][23] The remaining enzyme activity might reflect this interaction. However, more research is needed to clarify the reason for this phenomenon.…”
Section: Discussionmentioning
confidence: 99%